PENGARUH KINERJA KEUANGAN DAN KINERJA NON KEUANGAN TERHADAP NILAI PERUSAHAAN ( STUDI EMPIRIS PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA ) - Ninik Karmila, 11.05.62.0004 (Students Journal of Accounting and Banking, 2013)
The objective of this study is to examine the influence of profitability, likuidity, leverage, dividend payout ratio, managerial ownership, institusional ownership and size to firm value among financial sector which listed on Indonesia Stock Exchange. The population is 60 companies of financial sector which listed on Indonesia Stock Exchange at period 2009 to 2011. Sample was chose using purposive sampling method amount to 19 companies.Technique test of data is by using multiple linear regression.The result indicates that profitability, dividend payout ratio and size is significant positively influence the firm value. Liquidity, leverage Managerial ownership and public ownership is significant negatively influence the firm value.Keywords: profitability, likuidity, leverage, dividend payout ratio, managerial ownership, institusional ownership, size and firm value